THE ANTIBACTERIAL ACTIVITY OF TRADITIONALLY USED SALVADORA PERSICA L. (MISWAK) AND COMMIPHORA GILEADENSIS (PALSAM) IN SAUDI ARABIA - Al-sieni, Abdulbasit (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Nowadays there is a need to find naturally occurring substances from plants with antimicrobial activity as an alternative to available used antibiotics. Materials and Methods: Salvadora persica (miswak) and Commiphora gileadensis were collected, dried and extracted with either methanol or warm water and the obtained extracts were assessed for their antibacterial activity against 5 different genera of bacteria using agar well diffusion method. The tested bacteria included some human pathogens. Results: The obtained extracts exhibited considerable inhibitory effects against all the tested bacteria with various degrees of growth inhibition. It was shown that methanol extract was more effective compared to water extracts. The minimum inhibitory concentrations (MIC) of the methanol extracts ranged from 50-100 µg/ml. No toxicity was found using Artimia salina as test organism and no antitumor activity against Ehrlich ascites carcinoma. Conclusion: S. persica and C. gileadensis showed moderate to high inhibitory activity on pathogenic bacteria with no toxicity and can be used traditionally as alternative medicine